Effect of Collagen Cross-Linking on Corneal Thickness in Children with Progressive Keratoconus: Collagen Cross-Linking on Corneal Thickness in Children with Progressive Keratoconus - Kumar, Nitin; Fatima, Anum; Tahir, Sidra; Sattar, Abdul; Ali, Irshad; Farrukh, Muhammad Salman (Pakistan Journal of Health Sciences, 2025)
CXL tends to alter the collagen of the cornea via alteration of biochemical properties in Keratoconus using assisted riboflavin and UVA. This causes an increase in rigidity of the cornea and slows the progression of the disease. Objectives: To analyze the mean changes in corneal thickness after Corneal Collagen Cross-Linking (CXL) among children aged 8 to 15 years diagnosed with Keratoconus. Methods: This quasi-experimental study was conducted at the Department of Cornea, Al-Ibrahim Eye Hospital, Karachi, from March–September 2022. A sample size of 34 was calculated using G Power software with 80% power and a 95% confidence level. Non-probability consecutive sampling was used. Pediatric patients (8–15 years) with progressive keratoconus were included, while those with other ectatic disorders, active ocular disease, or prior anti-glaucoma medication were excluded. Ethical approval and informed consent were obtained. Clinical assessments were done before and after CXL, with follow-ups at weeks 4 and 12. Data were analyzed using SPSS version 23.0, applying appropriate statistical tests. Results: The study observed a mild reduction in keratometric values (K1, K2, Kmax) and central corneal thickness following collagen cross-linking in 34 children with progressive keratoconus over three months. Although Kmax decreased from 56.3 ± 10.3 to 53.4 ± 8.9 and corneal thickness from 487.88 ± 31.66 µm to 485.73 ± 31.90 µm, these changes were not statistically significant, indicating early stabilization without significant structural alteration. Conclusions: Collagen cross-linking in children with progressive keratoconus appears to stabilize corneal curvature with minimal impact on central corneal thickness over a short-term period, though changes are not statistically significant.